Vplivi okoljskih dejavnikov na prostorsko razporeditev gamsa (Rupicapra rupicapra L.) v gozdnatem območju Jelovice z obrobjem - Hafner, Miran (Gozdarski vestnik, 2010)
The chamois (Rupicapra rupicapra L.) is a constitutive part of the fauna of numerous mountain ecosystems where it inhabits the areas with the altitude between 800 and 2300 m. In the studied area of Jelovica with the surface of ca. 58.000 ha it lives in the low mountain range. In the research we studied which environmental factors had key impact to its spatial distribution. The study is based on the sample N=524 georeferential taking locations and GIS data layers (18 environmental variables). The logistic regression anticipates the adequacy of the space for the chamois habitat to be conditioned by the values of 9 environmental factors. The analyses show the chamois densities to be the largest on the lower elevations on moderate slopes, in forests with lowplant species diversity, low forest edge density, rather large share of coniferous trees, low share of shallow soil, somewhat lower stand wood stock, in less illuminated stands and in stands with a moderate share of thick tress.
Keywords: zoogeografija; gamsi; Jelovica